Covalent organic frameworks: topological characterizations, spectral patterns and graph entropies - Arockiaraj, Micheal; Jency, Joseph; Mushtaq, Shagufa; Shalini, Arul Jeya; Balasubramanian, Krishnan (Journal of mathematical chemistry, 2023)
Donor–acceptor covalent organic frameworks are porous polymers that are covalently bonded through dative donor–acceptor bonds. These materials have been the subject of several studies because of their unusual properties that render them as candidates for a wide range of applications. We have considered metal phthalocyanine with diimide linkers as donor–acceptor covalent organic frameworks. Owing to their photoinduced charge separations and photoenergy conversions, these frameworks are vital components in the next-generation devices. Since these networks exhibit interesting topologies, and their topological structures are correlated to the underlying connectivity, the study of structure–property relations is of utmost importance. In the present study, we aim to determine the topological characterization and entropy measure of these frameworks through various degree based and scalar self-powered topological descriptors. Furthermore we obtain combinatorially enabled machine generated NMR and ESR spectral patterns.